FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PEDAGANG DALAM PELAKSANAAN PROTOKOL KESEHATAN COVID-19 DI PASAR PETISAH KOTA MEDAN SUMATERA UTARA - Rimenda Putri Tetartor; Isabela Anjani; Mafe Robbi Simanjuntak; Dameria . (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
Pasar Petisah is one of the markets in Medan City where PD Pasar requires traders to apply health protocols during the July purchase of goods. This study aims to determine education, knowledge, attitudes, social environment, and sources of information on Trader Compliance with the Implementation of the Covid-19 Health Protocol in Petisah Market, Medan City, North Sumatra. This type of research is a quantitative study using a cross sectional study design. The research sample consisted of 83 people. The results of this study were tested statistically using the Chi Square Test with a 95% confidence level using SPSS software. The results showed that the P-Value for education was 0.000 (0.000 <0.05), the P-Value for knowledge was 0.004 (0.004 <0.05), the P-Value for attitude was 0.000 (0.000 <0.05), the P-value for knowledge -The social environment value is 0.143 (0.143> 0.05), the P-value of the information source is 0.296 (0.296 <0.05). The conclusion is that there is a relationship between education, knowledge, and attitudes towards Trader Compliance with the Implementation of the Covid-19 Health Protocol in Pasar Petisah Kota Medan, North Sumatra, while the Social Environment and sources of information are not related to the Implementation of the Covid-19 Health Protocol in the Petisah Market, Medan City, North Sumatra. It is recommended that traders and the public are expected to increase their knowledge (understanding) about Covid-19 and continue to carry out the Covid-19 health protocol wherever they are in order to avoid the transmission of the Covid-19 disease.